Down-regulation of tinnitus negative valence through concurrent HD-tDCS and positive emotion induction: effects on neural and behavioral correlates - Vazirikangolya, Zahrasadat (2022)
Conscious attended awareness perception of subjective tinnitus, experienced as a ringing or buzzing sensation in the absence of an external source, influences roughly 30% of the general population. Patients with clinical distress tinnitus experience highly disruptive and debilitating situation making it more complicated than simply experiencing a phantom sound urging them to seek medical help. With its high prevalence and potentially devastating impact on a person\'s psychological well-being, the demand for an effective clinical treatment of tinnitus is highly prioritized. However, at present there is no universal cure specifically tailored for alleviating tinnitus distress. Our knowledge of tinnitus distress is still limited in terms of its underlying neural mechanisms and causes which necessitate the need for development of treatments, alleviating tinnitus distress. In light of the neurofunctional tinnitus model predictions and transcranial electrical stimulation application, we conducted a study concurrently utilizing high-definition transcranial direct current stimulation (HD-tDCS) and positive emotion induction (PEI) techniques for ten consecutive sessions to down-regulate tinnitus negative valence in patients with clinical distress tinnitus. We recruited resting-state functional magnetic resonance imaging scans of twelve patients before and after the intervention to examine resting-state functional connectivity (rsFC) alterations at specific seed regions. Results showed reduced rsFC at post between attention and emotion processing regions as follows: 1) bilateral amygdala and left superior parietal lobule (SPL), 2) left amygdala and right SPL, 3) bilateral dorsolateral prefrontal cortex (dlPFC) and bilateral pregenual anterior cingulate cortex (pgACC), 4) left dlPFC and bilateral pgACC. Moreover, Tinnitus Handicap Inventory scores were significantly lower at the post-intervention compared to pre-intervention. Conclusion: Concurrent HD-tDCS and PEI might be effective in reducing tinnitus negative valence, thus, alleviating the tinnitus distress.